Hubungan Umur Dan Pendidikan Dengan Parenting Selfefficacy Score Pada Ibu Muda - Oktaliana Oktaliana; Aryanti Wardiyah; Lidya Aryanti (Malahayati Nursing Journal, 2022)
ABSTRACT Accounting to world health organization (WHO) figures in 2011 in the US the incidence of postpartum depression was 43%, in Asia at 30%, in the UK in 2008-2009 the morbity rate due to childbirth increased to 24% from the previous 9% and in Australia, in 2007 the morbity and mortality due to childbirth also increased to 31% from the previous 21% and in Indonesia by 9.8% parenting self-efficacy will reduce the risk of postpartum depression, stress, and anxiety and are positively related to the well-being of parents. To know maternal age, education level, and parenting self-efficacy among adolescent mothers during the period at public Health Services(Puskesmas) Panjang Bandar Lampung 2021. This research type is quantitative (Non-Experimental) The Design in this study is an analytical survey with a cross-sectional approach, population, and sample of all postpartum young mothers are 66  people. Technical sampling purposive sampling. The result of a statistical test using chi-square. Keywords: Maternal Age, Education Level, Parenting Self-Efficacy, Postpartum ABSTRAK Data World Health Organization (WHO) tahun 2011 di Amerika Serikat kejadian depresi postpartum sebesar 43%, di Asia sebesar 30%, di Inggris tahun 2008-2009 angka kesakitan akibat persalinan meningkat menjadi 24% dari sebelumnya 9% dan di Australia pada tahun 2007.  angka kesakitan dan kematian akibat persalinan juga meingkat menjadi 31% daris ebelumnya 21%, dan di Indonesia sebesar 9,8% Parenting Self-efficacy yang tinggi akan menurunkan resiko terjadinya depresi post partum, stress, dan kecemasan dan berhubungan yang positif dengan kesejahteraan orang tua. Tujuan penelitian untuk mengetahui hubungan umur dan Pendidikan pada skala parenting self-efficacy pada ibu muda di Puskesmas Panjang Bandar Lampung tahun 2021. Jenis Penelitian ini adalah kuantitatif (non-eksperimen). Rancangan dalam penelitian ini Survei Analitik dengan pendekatan cross sectional, populasi dan sampel seluruh ibu muda sejumlah 66  orang. Teknik sampel purposive sampling. Hasil uji statistik menggunakan chi square. Ada hubungan antara umur terhadap parenting self-efficacy score. Kata Kunci: Umur, Pendidikan, Parenting Self-Efficacy, Post Partum